Evaluation of a Novel Infrared Thermography Projection to Assess Udder Health in Primigravid Dairy Heifers - Patrícia B. A. Simões; Lorenzo Viora; Pieter T. Pepler; Timothy Geraghty; Dominic J. McCafferty; Ruth N. Zadoks (Animals, 2022)
Heifer mastitis in early lactation impacts negatively on animal welfare, milk production and longevity. A major challenge for the prevention and control of mastitis in dairy heifers is to establish when intramammary infection occurs because pre-partum secretum sampling is risky. We evaluated a ventrodorsal projection to capture thermal images of the entire udder of primigravid and compared results against caudocranial projection, which is used in lactating cattle. Based on the analysis of 119 heifers and images taken at 2 months and 2 weeks pre-partum, a very strong positive correlation (r = 0.91 and r = 0.96, respectively) was shown between caudocranial and ventrodorsal projections of hind quarters. Quarter maximum gradient temperatures were consistently greater on ventrodorsal projection than on caudocranial projection, and less variable than minimum gradient temperatures. The collection of ventrodorsal images is a simple one-step method involving the imaging of the entire udder in a manner safe for both the cattle and handlers. Together, these results demonstrate that a single projection can be used to scan the entire udder of primigravid dairy heifers in commercial farm conditions, with the potential to implement this as a routine method for the early detection of intramammary infection based on udder surface temperature.